50. THE VALUE OF CONVENTIONAL ULTRASOUND AND ADVANCED TECHNIQUES IN THE DIAGNOSIS OF BILIARY ATRESIA (Vietnam Journal of Community Medicine, 2025)
Objectives: Assessing the value of ultrasound in diagnosing biliary atresia at the National Hospital of Pediatric from 2021 to 2023Methods: A cross-sectional study was carried out on 72 patients with cholestasis and had the final diagnosis of biliary atresia or not due to exploratory surgery associated with cholangiogram and had pathology results. All patients had been performing conventional and Doppler ultrasonography, Elastography due to BA protocol pre-operation.Results:  The irregular gallbladder wall’ sign has Se 81.2%, Sn 93.3%, PPV 96.3%,; gallbladder’s length
Keywords: Biliary atresia; ultrasonography; elastic graph; Doppler ultrasonography